2015
DOI: 10.2147/ott.s90213
|View full text |Cite
|
Sign up to set email alerts
|

Advanced lung adenocarcinoma with spinal cord metastasis successfully treated with second EGFR-TKI treatment: a case report and literature review

Abstract: Lung adenocarcinoma can be accompanied by epidermal growth factor receptor (EGFR) mutation. As a consequence, targeted therapy based on screening of tyrosine-kinase inhibitors (TKIs) is necessary. Spinal cord metastasis of lung cancer is a serious clinical problem. Here, we report a case of lung adenocarcinoma with severe spinal cord metastasis that was successfully treated with a second administration of an EGFR-TKI. Magnetic resonance imaging showed spinal cord metastasis to the cervical vertebrae. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, in cases in which the tumor burden is small and symptoms are minimal, the use of select, fast‐acting targeted agents may be feasible, particularly if the patient is not a suitable candidate for surgery or radiation. For instance, Li et al reported a partial response of a cervical metastatic lesion in a woman with presumed epidermal growth factor receptor–mutant lung adenocarcinoma after 4 months of erlotinib. Other targeted therapies such as BRAF inhibitors and anaplastic lymphoma kinase (ALK)/ROS inhibitors may also prove to be useful when the tumors harboring these alterations respond quickly to the targeted agents, although experience with these scenarios has not been frequently reported in the literature.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…However, in cases in which the tumor burden is small and symptoms are minimal, the use of select, fast‐acting targeted agents may be feasible, particularly if the patient is not a suitable candidate for surgery or radiation. For instance, Li et al reported a partial response of a cervical metastatic lesion in a woman with presumed epidermal growth factor receptor–mutant lung adenocarcinoma after 4 months of erlotinib. Other targeted therapies such as BRAF inhibitors and anaplastic lymphoma kinase (ALK)/ROS inhibitors may also prove to be useful when the tumors harboring these alterations respond quickly to the targeted agents, although experience with these scenarios has not been frequently reported in the literature.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Although neither case had EGFR mutations, including T790M, PFS after ISCM diagnosis was 7 years and 11 months, respectively. The reason for the administration of EGFR-TKI in the first case14 is unclear; however, its use in the second case13 was due to patient preference and favourable EGFR-TKI prognostic factors, including Asian ethnicity, presence of adenocarcinoma, female sex and lack of smoking history 16. Our case differs from these prior cases because the ISCMs appeared during the administration of EGFR-TKI (afatinib), suggesting that response to treatment with gefitinib or erlotinib would be unlikely.…”
Section: Discussionmentioning
confidence: 75%
“…Notably, only two cases of treatment of ISCMs secondary to lung adenocarcinoma with EGFR-TKIs (gefitinib or erlotinib) have been reported 13 14. Although neither case had EGFR mutations, including T790M, PFS after ISCM diagnosis was 7 years and 11 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important change during the last decade was the introduction of treatment guided by the genetic profile of the tumor (9). Treatment with EGFR-TKI such as gefitinib or erlotinib is an effective targeting therapy, particularly for advanced NSCLC (10). According to clinical characteristics of the patient and histological and genetic results, erlotinib was started as second-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%